Hasil Beberapa Kultivar Padi Gogo Lokal Terhadap Cekaman Kekeringan - Edi Cahyadi; Andi Ete; Sakka Samudin (Mitra Sains, 2020)
Increased rice production carried out by rice cultivation in dry land faces constraints of vulnerability to climate change, especially drought that can reduce production. This study aims to determine the results of some local upland rice cultivars and also their tolerance to drought stress. The study was conducted at the green house, Faculty of Agriculture, Tadulako University, Palu, from September 2018 to February 2019. This research was an experimental design research with a completely randomized design (RAL) factorial pattern. The first factor is the cultivar (K) of rice consisting of 4 namely Taku Rice, Uva Rice, Jahara Rice and Delima Rice. The second factor is drought stress (C) in the form of water supply based on field capacity consisting of four treatment levels of 100%, 85%, 70% and C3: 55%. The treatment of drought stress resulted in an increase in the percentage of empty grains, a decrease in the number of panicle grains and crop yields. The highest crop yields found in Delima rice cultivars were significantly different from Jahara rice but not significantly different from Taku and Uva rice. This is in line with the stress sensitivity index where Jahara rice is indicated to be vulnerable to drought stress.